PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MACTH UNTUKMENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGER I21 BALAI MAKAM KECAMATAN MANDAU - Masdarita Masdarita; Syahrilfuddin Syahrilfuddin; Hamizi Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The problem this research is the student achievement of social studiesthree graderes SDNegeri21 Balai Makam still low with an average value of 65,3 and KKM social studies is 70. This research is Classroom action Research (CAR), wich aims to improve the learning process in the classroom. Based on the conduct of research with the implementation of learning models obtained results koopertif Make a Macth type of activity the teacher in the lerning process in cycle I frist meeting was 58,33% and at the second meeting of teacher activity increased to 66,67%. cycle II firs meeting and the second meeting of activity increased to 87,50% and the second meeting of activity increased to 95,83%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 50% and at second meeting of activity increased to 58,33%% and a second meeting of activity increased to 79,17%. At the firs meeting of the second meeting of activity increased to91,67%.This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 65,3. In the first cycle improve an average of 72,8and an impove in the second with an average of 79,7 with increase as 22,05%. Result in the research that the implementation of cooperative learning model of Make a Macth can improve students achievement of social Studies at three graderes SDNegeri21 Balai Makam Kecamatan Mandau.Key Words: Model Learning Make a Macth, IPS learning outcomes.